TINJAUAN SOCIO LEGAL KEBIJAKAN PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL (PPKS) DI PERGURUAN TINGGI KEAGAMAAN ISLAM (PTKI) – SK DIRJEND PENDIS KEMENAG RI – DRAFT PERATURAN REKTOR TENTANG PPKS - Muhammad Jailani (Pusat Studi Gender dan Anak, 2020)
It is a fact that University, even Islamic University under the authority of Religious Ministry Institution, is not free from the incident of sexual violence, yet they don’t have rulings and procedure of preventing and handling the case of sexual violence involving civitas academic, be it happen inside or outside the campus. For this reason, it is crucial to conduct an analysis on the document of Preventing and Handling the Sexual Violence (PPKS) rules in National Islamic Higher Education with relate to the Decree of the General Director of Islamic Education on PPKS in PTKI and National regulations. This study method uses descriptive qualitative analysis with a socio-legal approach. The data sources are field data on sexual violence and harassment research in 2019 and 2020 and library documents. From the findings and socio-legal analysis, it is known that Indonesia's positive law is still partial and does not provide sufficient detail regarding the prevention and management of sexual violence. The Decree of the Director-General of Pendis uses the definition of the form of sexual violence referring to the Bill on the Elimination of Sexual Violence, where on the one hand it takes sides with victims and human rights but on the other hand, has potential problems in the application of the Decree of the Director-General of Pendis in the future. The Draft of a decree or existing decree of the rector at PTKI, including at UIN SU, try to refer to the Decree of the Director-General of Education, especially in the juridical, sociological, philosophical aspects as well as the benefit to victims and the academic community. However, in-depth analysis of the draft of the rector's regulation does not fully comply with the Decree of the Director-General of Education, particularly in the aspects of the referral service system, PPKS management structure, and monitoring and evaluation mechanisms.